Concept of the Natural Structure of Engineering Training and the Code of Professional Ethics of an Engineer - R Dreher; A. O. Gornov; V. V. Kondratyev (Высшее образование в России)
The paper focuses on challenges and problems of modern engineering education. The necessity of designing and constructing a new model of the educational system related to the survival of humanity and training of engineers of a new type is substantiated. The global trends in the development of engineering education, trends and requirements for the competencies of future engineers are characterized. As one of the concepts for the development of engineering education, the concept of the natural structure of engineering training (NL) has been considered. The main innovative components of the NL concept are highlighted. Based on the code of professional ethics of an engineer, the main provisions of the Leonardo oath for engineers are formulated as a reference for curricula in engineering education.